PENERAPAN MODEL MIND MAPPING TERHADAP PEMBELAJARAN TEKS EKSPLANASI PADA PESERTA DIDIK KELAS XI SMA LABORATORIUM UPGRIS TAHUN 2022/2023 - Yulia Syafitri; Raden Yusuf Sidiq Budiawan; Latif Anshori Kurniawan (Jurnal Tunas Pendidikan, 2023)
The purpose of the study was to describe the application of the Mind Mapping model in learning explanatory texts for class IX students of SMA Laboratorium UPGRIS in the 2022/2023 academic year. This study uses a mixed method. Test and non-test techniques were used to collect research data and data were analyzed using triangulation techniques. Presentation of research data using formal and informal techniques. The results of the study showed that the Mind Mapping model can be applied to learning explanatory texts for class IX students of SMA Laboratorium UPGRIS in the 2022/2023 academic year. Based on the test results, the average pretest score was 66.62 and the average posttest was 78.22, from the test results there was an increase in students' explanatory text learning outcomes by 12.34%. Based on the results of observations and distribution of questionnaires to students and educators, the findings of the study showed that the Mind Mapping learning model can be used in learning explanatory texts because it can improve students' abilities in compiling explanatory texts, encourage students' involvement in learning to be more active, increase students' creativity in thinking, make it easier for students to understand the subject matter of explanatory texts and can improve students' learning outcomes in explanatory texts. This is evidenced by the activeness of students when participating in learning and the increase in the average value of explanatory texts produced by students.